Analisis Penerapan Mobile Marketing pada Era Society 5.0 melalui Kopra by Mandiri di KCU Plaza Mandiri Jakarta - Febi Aulia; Paidil Akbar Batubara; Ryan Aditya Alfasha; Hasyim Esty (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2024)
This research aims to analyze the application of mobile marketing in the Society 5.0 era through the Kopra by Mandiri application at KCU Plaza Mandiri Jakarta. By utilizing advances in digital technology, Kopra offers various features to increase the efficiency of banking services and make it easier for customers to carry out transactions. A descriptive qualitative approach was used in this research, through interviews and literature studies. Data analysis shows that digital transformation significantly increases customer satisfaction, with varying effects depending on the features used in Kopra by Mandiri services. The research results show that the Kopra application can increase the accessibility of financial services and support business actors, but is also faced with challenges such as the need for technological adaptation and data privacy concerns. This research recommends developing a more personalized marketing strategy and collaborating with the digital ecosystem to strengthen Bank Mandiri's position in the competitive banking industry. Keywords: Mobile Marketing, Era Society 5.0, Kopra by Mandiri